1994
DOI: 10.1002/1097-0142(19940415)73:8<2168::aid-cncr2820730822>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and mortality from breast cancer in the mama program for breast screening in Finland, 1973–1986

Abstract: Background. A cohort of women enrolled in the Mama breast self‐examination‐(BSE) containing breast screening program in Finland from 1973 through 1975 (with BSE used for screening and mammography for diagnosis) was studied. Methods. Twenty‐eight thousand seven hundred eighty‐five women who returned calendars recording their practice of BSE over a 2‐year period have been followed by linkage with the records of the Finnish Cancer Registry through 1986. The incidence of and mortality from breast cancer was compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0
3

Year Published

1995
1995
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(37 citation statements)
references
References 13 publications
3
31
0
3
Order By: Relevance
“…BSE has certain limitations; today, it is considered as an auxiliary method for essential breast cancer screening methods (26,27). There are several studies from the past mentioning the effectiveness of BSE and the requirement to recommend its administration (6,28,29). It is a economical method that is easy to implement and keeps the patients' awareness alive.…”
Section: Discussionmentioning
confidence: 99%
“…BSE has certain limitations; today, it is considered as an auxiliary method for essential breast cancer screening methods (26,27). There are several studies from the past mentioning the effectiveness of BSE and the requirement to recommend its administration (6,28,29). It is a economical method that is easy to implement and keeps the patients' awareness alive.…”
Section: Discussionmentioning
confidence: 99%
“…Alcohol consumption increases the risk of breast cancer (Anstey and Cheurbin, 2010;Tamimi et al, 2005). A cohort study in Finland (Gastrin et al,1994) and a case control study in Canada (Harvey et al,1997) suggested Breast self Examination to be beneficial (reduction in breast cancer mortality) at all ages. Regarding secondary prevention, Breast Self Examination may be the most effective approach in much of Asia, if only to improve awareness and early presentation at hospital when symptoms are detected (Moore and Sobue, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Cohort studies of women with and without breast cancer The two cohort studies were from Finland (Gastrin et al, 1994) and the USA (Holmberg et al, 1997). In these, breast cancer death rates according to BSE practice were reported in populations of women followed up for over 13 years.…”
Section: Methods Data Sources and Study Selectionmentioning
confidence: 99%
“…In these, breast cancer death rates according to BSE practice were reported in populations of women followed up for over 13 years. In one study (Gastrin et al, 1994), mammography was used only as a method of further investigation after a woman found a lump by BSE. In the other study, the followup period was until 1972 when mammography was not commonplace.…”
Section: Methods Data Sources and Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation